Identification, characterization and antigenicity of the Plasmodium vivax rhoptry neck protein 1 (PvRON1) (2011)
Background: Plasmodium vivax malaria remains a major health problem in tropical and sub-tropical regions worldwide. Several rhoptry proteins which are important for interaction with and/or invasion of red blood cells, such as PfRONs, Pf92, Pf38, Pf12 and Pf34, have been described during the last few years and are being considered as potential anti-malarial vaccine candidates. This study describes the identification and characterization of the P. vivax rhoptry neck protein 1 (PvRON1) and examine its antigenicity in natural P. vivax infections. Methods: The PvRON1 encoding gene, which is homologous to that encoding the P. falciparum apical sushi protein (ASP) according to the plasmoDB database, was selected as our study target. The pvron1 gene transcription was evaluated by RT-PCR using RNA obtained from the P. vivax VCG-1 strain. Two peptides derived from the deduced P. vivax Sal-I PvRON1 sequence were synthesized and inoculated in rabbits for obtaining anti-PvRON1 antibodies which were used to confirm the protein expression in VCG-1 strain schizonts along with its association with detergent-resistant microdomains (DRMs) by Western blot, and its localization by immunofluorescence assays. The antigenicity of the PvRON1 protein was assessed using human sera from individuals previously exposed to P. vivax malaria by ELISA. Results: In the P. vivax VCG-1 strain, RON1 is a 764 amino acid-long protein. In silico analysis has revealed that PvRON1 shares essential characteristics with different antigens involved in invasion, such as the presence of a secretory signal, a GPI-anchor sequence and a putative sushi domain. The PvRON1 protein is expressed in parasite's schizont stage, localized in rhoptry necks and it is associated with DRMs. Recombinant protein recognition by human sera indicates that this antigen can trigger an immune response during a natural infection with P. vivax. Conclusions: This study shows the identification and characterization of the P. vivax rhoptry neck protein 1 in the VCG-1 strain. Taking into account that PvRON1 shares several important characteristics with other Plasmodium antigens that play a functional role during RBC invasion and, as shown here, it is antigenic, it could be considered as a good vaccine candidate. Further studies aimed at assessing its immunogenicity and protection-inducing ability in the Aotus monkey model are thus recommended.